Steel Rigid Frames With Leaning Columns—1993 LRFD Example - Folse, Michael D.; Nowak, Paul S. (Engineering Journal, 1995)
Many buildings rely on rigid frames to provide lateral stability in one or both directions. Steel rigid frames often support "leaning" columns which hold their contributory gravity loads but rely on the frame for lateral stability. Rigid frames supporting leaning columns require special consideration whether a first-order or second-order analysis is undertaken. The design and analysis of rigid frames with leaning columns in accordance with the 1993 AISC LRFD is studied through use of an example eight story steel building which is supported laterally in each direction by isolated rigid frames. Results of first-order analyses with approximate moment magnification are compared with plane frame and space frame second-order elastic analyses.